2019
DOI: 10.3390/pharmaceutics11080423
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Subcellular Trafficking of Resveratrol Using Mitochondriotropic Liposomes in Cancer Cells

Abstract: Mitochondria are membrane-enclosed organelles present in most eukaryotic cells, described as “power houses of the cell”. The mitochondria can be a target for inducing cancer cell death and for developing strategies to bypass multi drug resistance (MDR) mechanisms. 4-Carboxybutyl triphenylphosphonium bromide-polyethylene glycol-distearoylphosphatidylethanolamine (TPP-DSPE-PEG) and dequalinium-polyethylene glycol-distearoylphosphatidylethanolamine (DQA-DSPE-PEG) were synthesized as mitochondriotropic molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The enhanced uptake was also demonstrated by LCMS/MS quantified resveratrol in the subcellular organelles. The mitochondrial membrane dissipation, ROS production, and cell cytotoxicity results demonstrated that these liposomes can provide a vital subcellular targeting strategy in the cancer treatment (Kang and Ko, 2019).…”
Section: Current Scenario Of Subcellular Drug Targetingmentioning
confidence: 99%
“…The enhanced uptake was also demonstrated by LCMS/MS quantified resveratrol in the subcellular organelles. The mitochondrial membrane dissipation, ROS production, and cell cytotoxicity results demonstrated that these liposomes can provide a vital subcellular targeting strategy in the cancer treatment (Kang and Ko, 2019).…”
Section: Current Scenario Of Subcellular Drug Targetingmentioning
confidence: 99%
“…Recently, it was demonstrated that TPP, as part of the vectors, can transfer chemotherapeutic drugs into cancer cells and simultaneously target mitochondria in cancer cells [25]. In this study, F127 was conjugated to COOH-TPP by esterification using DCC/DMAP.…”
Section: Synthesis and Characterization Of Tph/ptxmentioning
confidence: 99%
“…Twenty tumor-bearing mice (A549/ADR) were used when the volume of the tumors reached approximately 220-230 mm 3 . The animals were randomly divided into four groups, namely, groups treated with saline, Taxol, TP/PTX, and TPH/PTX nanomicelles (n = 5), and treated at days 17,19,21,23,25,27, and 29 via the tail vein. The final concentration of PTX was 10 mg/kg.…”
Section: Antitumor Efficacy In Vivomentioning
confidence: 99%
“…Resveratrol-loaded nanocarriers effectively deliver resveratrol into mitochondria of cancer cells. Resveratrol promotes the generation of ROS to depolarize the mitochondrial membrane resulting in apoptotic cell death [221]. Loading resveratrol on the mitochondrial-targeted titanium disulfide nanosheets is another potential strategy in cancer chemotherapy.…”
Section: Selective Targeting Of Mitochondria In Cancer Therapy Using mentioning
confidence: 99%